Raske drenge og syge piger: På grænsen mellem sundt og sygt i 1800-tallets visuelle kultur - Bøgh Jensen, Mette (K&K - Kultur og Klasse, 2021)
This article analyzes how the two figures ‘healthy boy’ and ‘invalid girl’ are negotiated visually at the end of the nineteenth century and how the idea of being healthy or the opposite relates to these two figures. The center of the analysis are illustrations of invalid girls and healthy boys printed in the Scandinavian periodical Nordisk Illustreret Børneblad. The article pays attention to how the two figures are portrayed and examine which images of health and illness, parents and their children were presented to. The argument is that there is a close connection between the visual idea of the invalid girl and the healthy boy and the popular medical literature in the period, and that the idea of the invalid girl was being communicated not only in the paintings of the period but also as reproductions e.g. in children’s periodicals and thereby reached a larger audience.